THERORETICAL BASICS OF OPERATING HOTEL BUSINESS - Karimov Abdusamat (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2026)
This article explores the theoretical foundations of operating a hotel business, focusing on the core principles that shape effective management and service delivery. It begins by examining the structural components of hotel operations, including front office management, housekeeping, food and beverage services, and guest relations. The discussion highlights how strategic planning, staff coordination, and quality control contribute to overall performance. Emphasis is placed on the importance of customer satisfaction, operational efficiency, and adaptability to market trends. By analyzing these elements, the article aims to provide a conceptual framework for understanding how hotels function as dynamic service systems within the broader hospitality industry.